(untitled) (Journal of Global Accounting, 2023)
Capital structure decision is one of the basic decisions in a firm and liquidity management is known to affect corporate finance. Empirical studies in this area are noted to be insufficient in Nigeria, especially for firms with low profitability profile. This study examined the effect of cash conversion cycle on capital structure of manufacturing firms in Nigeria from 2012 to 2018. Three hypotheses were formulated for this study and tested using linear regression analyses at 5% level of significance. Ex-post facto (causal comparative) research design was adopted. The population and sample of the study is made up of the twenty – two quoted manufacturing firms on the Nigerian Stock Exchange as at year end 2018.The findings reveal that Receivables’ Collection Period, Inventory Turnover Period, and Payables Payment Period have a significant effect on components of capital. It is concluded that cash conversion cycle has significant effect on capital structure. This study recommends among others that manufacturing firms should decrease their inventory period and accounts receivables’ period, by instituting adequate control and flexible credit policy